Reimagining the Republic : Race, Citizenship, and Nation in the Literary Work of Albion W. Tourgée - Ball, Molly; Bentley, Nancy; Chakkalakal, Tess; Chinn, Sarah E.; Elliott, Mark; Ernest, John; Ewing, Annemarie Mott; Greeson, Jennifer Rae; Gustafson, Sandra M.; Gustafson, Sandra M.; Hale, Mary B.; Hale, Mary; et al. (Reconstructing America, 2022)
Albion W. Tourgée (1838-1905) was a major force for social, legal, and literary transformation in the second half of the nineteenth century. Best known for his Reconstruction novels A Fool's Errand (1879) and Bricks without Straw (1880), and for his key role in the civil rights case Plessy v. Ferguson (1896), challenging Louisiana's law segregating railroad cars, Tourgée published more than a dozen novels and a volume of short stories, as well as nonfiction works of history, law, and politics. This volume is the first collection focused on Tourgée's literary work and intends to establish his reputation as one of the great writers of fiction about the Reconstruction era arguably the greatest for the wide historical and geographical sweep of his novels and his ability to work with multiple points of view. As a white novelist interested in the rights of African Americans, Tourgée was committed to developing not a single Black perspective but multiple Black perspectives, sometimes even in conflict. The challenge was to do justice to those perspectives in the larger context of the story he wanted to tell about a multiracial America. The seventeen essays in this volume are grouped around three large topics: race, citizenship, and nation. The volume also includes a Preface, Introduction, Afterword, Bibliography, and Chronology providing an overview of his career. This collection changes the way that we view Tourgée by highlighting his contributions as a writer and editor and as a supporter of African American writers. Exploring the full spectrum of his literary works and cultural engagements, Reimagining the Republic: Race, Citizenship, and Nation in the Literary Work of Albion Tourgée reveals a new Tourgée for our moment of renewed interest in the literature and politics of Reconstruction.